Offshore Technology Conference 1981
DOI: 10.4043/3991-ms
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-Induced Vibrations Of A Flexible Cylinder Near A Plane Boundary In Steady Flow

Abstract: Model tests were carried out in a current tank to determine the effect of the proximity of a plane boundary on the vortex-induced vibrations of a flexible pipe.The response of the center of the pipe span was measured using an optical tracking system.It was found that in the presence of a plane boundary, the maximum amplitude of vibration is limited, and the onset of vortex-induced vibrations of appreciable amplitude occurs at higher velocities than when no boundary is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…While the initial gap is larger than about 0.3D, the vortex shedding frequency is affected slightly by the boundary [27][28][29][30]. It has been reported that the maximum response amplitude takes place at the larger reduced velocity V r (V r = U/( f n D), U is the flow velocity, f n is the natural frequency of the cylinder, D is the cylinder diameter) due to the influence of the wall [31,32]. Jacobsen et al [33] studied the amplitude response of a cylinder suspended in a spring system with gap-to-diameter ratios equal to 0, 0.5 and 1.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While the initial gap is larger than about 0.3D, the vortex shedding frequency is affected slightly by the boundary [27][28][29][30]. It has been reported that the maximum response amplitude takes place at the larger reduced velocity V r (V r = U/( f n D), U is the flow velocity, f n is the natural frequency of the cylinder, D is the cylinder diameter) due to the influence of the wall [31,32]. Jacobsen et al [33] studied the amplitude response of a cylinder suspended in a spring system with gap-to-diameter ratios equal to 0, 0.5 and 1.…”
Section: Introductionmentioning
confidence: 96%
“…Jacobsen et al [33] studied the amplitude response of a cylinder suspended in a spring system with gap-to-diameter ratios equal to 0, 0.5 and 1. Based on the work by Tsahalis and Jones [31,32] and Jacobsen et al [33], Fredsoe et al [34] investigated the cross-flow vibration of cylinders near a wall, and their study indicated that the transverse vibration frequency is close to the frequency of vortex shedding from a stationary cylinder, when reduced velocity is less than the value of 3 and the initial gap between the cylinder and the wall (e 0 ) is more than 0.3D; For the case of 3 < V r < 8 and 0 < e 0 < 1D the transverse vibrating frequency is noticeably larger than the frequency of vortex shedding from a stationary cylinder. Raven and Stuart [36] carried out the full-scale tests upon the vortex-induced vibration of the pipeline, and they indicated that the critical V r number for the occurrence of vibration would be affected by the initial gap.…”
Section: Introductionmentioning
confidence: 99%
“…These include: intermittent wave loading in the splash zone of surface-piercing members of structures [22], nonlinear effects stemming from finite amplitude waves such as second-order wave forces [10,23] and from finite displacements, and vortex-induced vibrations of (members of) structures exposed to current [24]! Solutions to these problems are not discussed in this paper.…”
Section: Other Nonlinearitiesmentioning
confidence: 99%
“…Wilson and Caldwell (1971) and King and Jones (1980) preliminarily studied the effect of the proximity to a plane boundary on the vortex-induced vibration of flexible cylinders exposed to steady flow experimentally. Tsahalis and Jones (1981) investigated the VIV of a flexible cylinder with e 0 /D = 1.0~6.0 in steady currents, and found that the maximum amplitude occurred at a higher value of reduced velocity and the maximum amplitude is reduced due to the proximity to the boundary. However, the results by Wilson and Caldwell (1971), King and Jones (1980) and Tsahalis and Jones (1981) did not present the vibration characteristics of the cylinder in streamwise direction, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Tsahalis and Jones (1981) investigated the VIV of a flexible cylinder with e 0 /D = 1.0~6.0 in steady currents, and found that the maximum amplitude occurred at a higher value of reduced velocity and the maximum amplitude is reduced due to the proximity to the boundary. However, the results by Wilson and Caldwell (1971), King and Jones (1980) and Tsahalis and Jones (1981) did not present the vibration characteristics of the cylinder in streamwise direction, respectively. Later, Tsahalis (1984) studied the vibration amplitude and frequency of a flexible cylinder with e 0 /D = 1 and in streamwise and transverse directions under the action of steady currents respectively, and found that the proximity to the plane boundary has a pronounced effect on the amplitude response in both directions.…”
Section: Introductionmentioning
confidence: 99%